Ответ:
Применяем формулы разности косинусов и разности синусов :
[tex]\bf cos\alpha -cos\beta =-2\cdot sin\dfrac{\alpha +\beta }{2}\cdot sin\dfrac{\alpha -\beta }{2}\ \ ,\\\\\\sin\alpha -sin\beta =2\cdot sin\dfrac{\alpha -\beta }{2}\cdot cos\dfrac{\alpha +\beta }{2}[/tex] .
[tex]\bf \dfrac{cos68^\circ -cos22^\circ }{sin68^\circ -sin22^\circ }=\dfrac{-2\cdot sin\dfrac{68^\circ +22^\circ }{2}\cdot sin\dfrac{68^\circ -22^\circ }{2}}{2\cdot sin\dfrac{68^\circ -22^\circ }{2}\cdot cos\dfrac{68^\circ +22^\circ }{2}}=\\\\\\=-\dfrac{sin45^\circ \cdot sin23^\circ }{sin23^\circ \cdot cos45^\circ }=-tg45^\circ =-1\\\\\\-1=-1[/tex]
Тождество доказано .
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Verified answer
Ответ:
Применяем формулы разности косинусов и разности синусов :
[tex]\bf cos\alpha -cos\beta =-2\cdot sin\dfrac{\alpha +\beta }{2}\cdot sin\dfrac{\alpha -\beta }{2}\ \ ,\\\\\\sin\alpha -sin\beta =2\cdot sin\dfrac{\alpha -\beta }{2}\cdot cos\dfrac{\alpha +\beta }{2}[/tex] .
[tex]\bf \dfrac{cos68^\circ -cos22^\circ }{sin68^\circ -sin22^\circ }=\dfrac{-2\cdot sin\dfrac{68^\circ +22^\circ }{2}\cdot sin\dfrac{68^\circ -22^\circ }{2}}{2\cdot sin\dfrac{68^\circ -22^\circ }{2}\cdot cos\dfrac{68^\circ +22^\circ }{2}}=\\\\\\=-\dfrac{sin45^\circ \cdot sin23^\circ }{sin23^\circ \cdot cos45^\circ }=-tg45^\circ =-1\\\\\\-1=-1[/tex]
Тождество доказано .